Forma incorporada: um olhar sobre a relação forma e conteúdos expressivos no corpo cênico - Tania Mara Silva Meireles (2010)
This research aimed to investigate form as a possible element of developing the stage performers consciousness and visual sensitivity. Form should be understood here as the inner and essential structure to construct space and materials in which will reflect the artists subjective impression. His/Her way of shaping space will reveal his/her thoughtsand sensation. In this work, both artistic and visual processes are based on the principles of visual perception and the complex semiotics of a theatrical event. Thus, Gestalt theory will be used to elucidate the relationship between psychophysical perception and form. Besides, Ernani de Castro Malettas Polyphonic Performance Concept helps to explain and justify the presence of various voices in the making up of a theatrical phenomenon. Finally, Wassily Kandinskys Theory of Forms synthesizes those constituent elements of plastic and scenic arts. As a result of such analysis, a term is created, namely Corpoforma (bodilyformed). This not only helps distinguishing the dialogic artistic and theoretical aspects involved in such a discussion, but also encourage to reflection as well as to generate procedures that may lead to the understanding and a conscious use of form in the scenic body. It, consequently, will improve an organic organization involving form and expressive contents.